Dinâmica do nitrogênio em sistemas de produção sob semeadura direta - Castoldi, Gustavo [UNESP] (2014)
Nitrogen cycling in the soil-plant system is quite complex, with diverse paths of input and output, and changes in soil and/or crop management can modify its dynamics affecting the N gain/losses balance. The integrated evaluation of these processes is essential for a better understanding of the N cycling in agricultural production systems. Our study aimed to evaluate N dynamics in soybean cropping systems in rotation with cover crops, with a focus on how the systems affect soil N storage and the major N losses from the soil-plant system. The experiment was carried out in a clay Rhodic Ferralsol, in Botucatu, São Paulo, Brazil. The experimental area has been cropped under no till for thirteen years, and the current treatments have been conducted since 2006. Congo grass (Brachiaria ruziziensis), grain sorghum (Sorghum bicolor) and a mix of both were cropped during fall/winter. In the spring, pear millet (Pennisetum glaucum), forage sorghum (Sorghum bicolor) and Sunn hemp (Crotalaria juncea) were cropped in sub-plots. Soybean (Glycine max) was cropped as summer crop. We assessed for two years the grain yield, dry matter, N accumulation and C/N ratio of the cropped species, as well as the soil N storage. We also quantified, for one year, N inputs via seeds, atmospheric deposition and pesticide spraying and N via NO3- leaching, NH3 emission from straw and above part of the plants and N2O emission from soil. Generally speaking, losses of N as NO3-, NH3 and N2O ranged, respectively, from 11.2 to 24.2, 19.0 to 10.6 and 1.2 to 9.7 kg ha-1 year-1, being the highest values observed in systems with Congo grass cropped in the fall/winter and Sunn hemp cropped in the spring season. These losses seem to have occurred due the highest N accumulation by these species. In the case of Sunn hemp, the largest contribution of N, even if it results in major losses, proved to be crucial for the positive balance of N in the ...